Temporal dynamics of visual representations in the infant brain. (October 2020) - Bayet, Laurie; Zinszer, Benjamin D.; Reilly, Emily; Cataldo, Julia K.; Pruitt, Zoe; Cichy, Radoslaw M.; Nelson, Charles A.; Aslin, Richard N.
Highlights: Access to infants' multivariate neural representations has remained limited. Visual stimuli decoded from 12−15-month-olds' EEG data, within 500 ms of onset. Infant multivariate representations didn't linearly separate animal and body images. Proof-of-concept for time-resolved multivariate pattern analysis of infant EEG. Abstract: Tools from computational neuroscience have facilitated the investigation of the neural correlates of mental representations. However, access to the representational content of neural activations early in life has remained limited. We asked whether patterns of neural activity elicited by complex visual stimuli (animals, human body) could be decoded from EEG data gathered from 12−15-month-old infants and adult controls. We assessed pairwise classification accuracy at each time-point after stimulus onset, for individual infants and adults. Classification accuracies rose above chance in both groups, within 500 ms. In contrast to adults, neural representations in infants were not linearly separable across visual domains. Representations were similar within, but not across, age groups. These findings suggest a developmental reorganization of visual representations between the second year of life and adulthood and provide a promising proof-of-concept for the feasibility of decoding EEG data within-subject to assess how the infant brain dynamically represents visual objects.